Design and evaluation of a novel process for the recovery of Cu and Au from waste printed circuit boards - Mukuna, Marco Ngeleka (Department of Chemical Engineering, 2025)
Au recovery is one of the most important aspects of an industrial-scale waste printed circuit board (WPCB) recycling operation because Au is a highly economically valuable metal which is present in WPCBs in appreciable concentrations, often tens to hundreds of times greater than in naturally occurring ore deposits. Unfortunately, significant value loss and resource wastage occurs when Au is recovered from WPCBs in conventional processing plants which use various pyrometallurgy and physical separation techniques. The primary aim of this project was to contribute knowledge to the development of a hydrometallurgical processing plant for Au recovery from WPCBs, which can be applied in real-life industrial-scale WPCB recycling operations, in a technically and economically feasible manner, as an alternative to conventional processing plants. To achieve this aim, findings from literature were used to successfully design a theoretical hydrometallurgical processing plant for Au recovery from WPCBs, which uses a non-toxic and recyclable iodide lixiviant for Au leaching and the novel ion-exchange extractant membrane solid-liquid extraction and electrowinning (IEM-SLE and EW) technique for Au concentration and recovery. The designed processing plant's early-stage technical feasibility assessment was supported by a laboratory experiment investigating the recovery of Au from WPCB iodide leachates using the IEM-SLE and EW technique. This laboratory experiment commenced by loading 2.0 L of WPCB iodide leachate into the feed tank of the experimental IEM-SLE and EW cell (IX-EW cell) and loading 2.0 L of KI-I2 electrolyte solution into the electrolyte solution tanks hosting the cathode and anode. Thereafter, electrical power was provided to the electrodes at a constant cell voltage of 12.9 V, temperature of 25 oC, 250 rpm agitation speed, average current of 5 A, and 1429 A/m2 equivalent current density. Once the experiment was complete/electrical power had been provided for 6.0 hrs, the brown Au deposit on the cathode was chemically analysed together with the sample electrolyte solutions collected from each of the IX-EW cell's tanks (after 2 hrs, 4 hrs, and 6 hrs). The laboratory experiment results demonstrated that Au recovery from WPCB iodide leachates using the IEM-SLE and EW technique is technically feasible since it was possible to concentrate and recover Au under the given conditions with a high yield (95.5 %) while recycling/recovering an iodide solution with an 82 % I2 recovery yield and 89 % I– recovery yield. However, due to the high voltages applied (12.9 V) and due to the loss of Au (~4 %) to the Au-IEM, it is evident that more research is required to optimise the developed processing plant before it can be subjected to a thorough technical and/or economic feasibility assessment, for application in a real-life industrial-scale WPCB recycling operation, in a technically and economically feasible manner. Through a discounted cash flow and profitability (DCFP) assessment, the early-stage economic feasibility of the processing plant under ideal conditions was successfully determined within a South African context. Results of the DCFP assessment showed that the processing plant's estimated NPV was $5,812,000,000 at a bond interest rate of 9 %, a cash flow discount rate of 17.86 %, and a corporate tax rate of 15 %. While the processing plant's ROI, PBP, net margin, and ebitda margin were estimated to be 76.00 %, 0.03 years, 34.74 % and 48.37 %, respectively. The observed short PBP and large positive NPV, ROI, net margin, and ebitda margin, suggest that the developed processing plant is economically feasible under the ideal specified plant design conditions. However, the sensitivity analysis of the processing plant's early-stage economic feasibility assessment shows that the developed processing plant is likely to be economically unfeasible for industrial-scale application under non-ideal conditions in a real-life setting since the annual revenue obtained from the recovery of Au from typical/non-ideal WPCBs is unlikely to result in pay back or produce a large positive NPV, ROI, ebitda margin, or net margin. The results of the sensitivity analysis showed that the processing plant's economic feasibility is highly sensitive to the key assumptions used in the design and development, and economic feasibility assessment, and in particular assumptions relating to annual revenue. Therefore, any future research and development should carefully review and ensure that any assumptions used are as accurate as possible. From the findings presented in this thesis, it is evident that the developed processing plant justifies further research and development for future application in real-life industrial-scale WPCB recycling operations. This is because the developed processing plant has the potential to be applied industrially in a technically and economically feasible manner as evidenced by the results of the project's early-stage technical and economic feasibility assessment.